2015
DOI: 10.1016/j.jnucmat.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Accurate lattice parameter measurements of stoichiometric uranium dioxide

Abstract: The paper presents and discusses lattice parameter analyses of pure, stoichiometric UO2. Attention was paid to prepare stoichiometric samples and to maintain stoichiometry throughout the analyses. The lattice parameter of UO2.000 ± 0.001 was evaluated as being 547.127 ± 0.008 pm at 20 °C, which is substantially higher than many published values for the UO2 lattice constant and has an improved precision by about one order of magnitude. The higher value of the lattice constant is mainly attributed to the avoidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 38 publications
(52 reference statements)
9
75
3
2
Order By: Relevance
“…Single crystal x-ray diffraction (XRD) measurements yield a lattice constant of 5.4703 ± 0.0006 Å for crystals produced under these growth conditions indicating a stoichiometry of UO 2.003 [15,25]. X-ray fluorescence (XRF) analysis indicated the crystal was of high purity (see supplementary materials (stacks.iop.org/JPhysCM/29/035005/mmedia)).…”
Section: Physical Characterizationmentioning
confidence: 99%
“…Single crystal x-ray diffraction (XRD) measurements yield a lattice constant of 5.4703 ± 0.0006 Å for crystals produced under these growth conditions indicating a stoichiometry of UO 2.003 [15,25]. X-ray fluorescence (XRF) analysis indicated the crystal was of high purity (see supplementary materials (stacks.iop.org/JPhysCM/29/035005/mmedia)).…”
Section: Physical Characterizationmentioning
confidence: 99%
“…The analysis was successful in avoiding false minima in the fitting space and eliminated researcher bias in parameter selection. While both XRD and EXAFS confirmed that the ThO 2 is in the fluorite structure, the EXAFS data confirmed the existence of local order distortions, particularly O atoms not on a traditional 1 , , unit cell site.…”
Section: Resultsmentioning
confidence: 83%
“…1 Introduction UO 2 compounds oxidize readily to form hyper-stoichiometric UO 2+x structures, as previous studies on the U-O system attest [1][2][3][4]. The tendency of these compounds to form defect centers is due to the multiple valence states available to the U atoms, with the 5f electron activity stabilizing interstitial O atoms.…”
mentioning
confidence: 99%
“…For accurate analysis of UO 2 -based systems, it is necessary to avoid stoichiometry variations resulting from air exposure. It was shown by Leinders et al that samples without open porosity remain stable over several weeks [15]. Most of the ThO 2 eGd 2 O 3 specimens reached more than 95% T.D.…”
Section: Sample Synthesis and Oxygen Equilibrationmentioning
confidence: 91%